System nauczania rachunkowości w USA - Grabiński, Konrad; Kędzior, Marcin (Accounting Education System in United States, 2005)
In the article accounting education system in United States has been presented and its evolution in the context of "Enron" crisis. Special attention has been focused on accountancy profession and its publicity, especially concerning trustworthiness issue. Secondly, the main determinants of accounting education system evolution have been identified: globalization, accounting development (theory and practice) and finally accounting computerization (i.e. Internet, ERP systems etc.). In the next part, new education methodological approaches have been characterized, including exemplified syllabuses. Finally, futurist challenges for education system have been pointed out, like i.e. XBRL (external Business Reporting Language) or CAATs (Computer Assisted Audit Techniques).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 52-62